On diffeomorfisms of almost quaternion manifolds(in Russian) - I. N. Kurbatova (Математичні Студії, 2013)
The special type mappings between Riemannian spaces with almost quaternion structure are studied. The fundamental theorems of theory of these mappings are proved.